2002
DOI: 10.1016/s0735-1097(02)01923-x
|View full text |Cite
|
Sign up to set email alerts
|

U-curve relationship between orthostatic blood pressure change and silent cerebrovascular disease in elderly hypertensives

Abstract: Silent cerebrovascular disease is advanced in elderly hypertensives having OHT. Elderly hypertensives with OHT or OHYPO may have an elevated risk of developing hypertensive cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
137
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 29 publications
10
137
2
12
Order By: Relevance
“…In a previous report, we had already observed a suppression of orthostatic SBP increase in elderly hypertensives with OHT following doxazosin administration. 5 However, in that previous study, we evaluated orthostatic SBP once before and once after the administration of doxazosin only. In contrast, in the present study, we included several observations obtained over a 6-month follow-up period, and it was found that the continuous administration of doxazosin successfully reduced not only sitting SBP but also the SBP increase while standing observed in OHT subjects throughout the follow-up period; furthermore, this amelioration of symptoms was seen with both clinic and home BP-monitoring modalities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous report, we had already observed a suppression of orthostatic SBP increase in elderly hypertensives with OHT following doxazosin administration. 5 However, in that previous study, we evaluated orthostatic SBP once before and once after the administration of doxazosin only. In contrast, in the present study, we included several observations obtained over a 6-month follow-up period, and it was found that the continuous administration of doxazosin successfully reduced not only sitting SBP but also the SBP increase while standing observed in OHT subjects throughout the follow-up period; furthermore, this amelioration of symptoms was seen with both clinic and home BP-monitoring modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that OHT might be associated with overactivity of the sympathetic nervous system. 1,5,27 Therefore, doxazosin might break the vicious cycle between the sympathetic nervous hyperactivity, orthostatic BP increase and renal damage by reducing both the orthostatic BP increase and excessive urinary albumin excretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations